Advances in the treatment and management of tetralogy of Fallot: Current and future perspectives (Research, Society and Development, 2024)
Advancements in the treatment and management of Tetralogy of Fallot (TOF) represent an area of significant importance in pediatric medicine, demanding a comprehensive and up-to-date understanding to ensure improvement in clinical outcomes and quality of life for affected patients. TOF is a complex congenital heart condition characterized by four specific abnormalities that compromise blood flow to the lungs, resulting in chronic hypoxemia and other cardiovascular complications. This work aims to analyze recent advancements and future perspectives in the treatment and management of TOF, one of the most prevalent congenital heart diseases in childhood. To achieve this, the main diagnostic methods, current therapeutic strategies, and emerging approaches in the management of this complex condition will be reviewed. To conduct the integrative review, a search was performed in the PubMed electronic database to identify relevant studies published in the last 10 years (2015 to 2024). The specific MESH descriptors used were "Tetralogy of Fallot," "Diagnostic," "Therapeutics," and "Drug therapy." These terms were selected to ensure the inclusion of studies addressing different aspects related to TOF, from new therapies to management guidelines and predictions for the future.